VALIDATION OF THE INTERNATIONAL AFFECTIVE PICTURE SYSTEM (IAPS) IN SERBIA: COMPARISON OF A SERBIAN AND A HUNGARIAN SAMPLE - Grabovac, Beata; Deák, Anita (Primenjena psihologija)
The purpose of this study was to extend the International Affective Picture System to Serbia, which is worldwide workrelated to the ratings. A total of 158 students participated in the study, which in- cluded ninety Hungarian students and sixty-eight Serbian students. The participants were required to rate sixty pictures from the IAPS database on the dimensions of valence, arousal and dominance. One of our main aims was to compare the results from Serbia and the North American ratings. We found a signifi group difference on the dimension of arousal between the North American and the Hungarian group. Additionally, we found differences between the two groups from Serbia: in Serbian and Hungarian students, as majority and minority groups, there were differences on a dimen- sion arousal. The differences that were statistically signifi in relation to the ratings from Hungary were the ones between the Hungarian group from Hungary and the North American ratings, as well as between the Hungarian group from Hungary and our Hun- garian group, on the dominance dimension. Sex differences were also found signifi regarding arousal and dominance. These differences were in line with other cross-cultural comparisons. We also correlated the results from the USA, Hungary, Bosnia, and our two subgroups, and we found the highest correlations between the two groups from Serbia. Based on the overall results we could conclude that the affective evaluations were similar in Serbia and in other countries, and that the IAPS database could be used for the research purposes in Serbia.